Ventricular Unloading Using the ImpellaTM Device in Cardiogenic Shock - Attinger-Toller, Adrian; Bossard, Matthias; Cioffi, Giacomo Maria; Tersalvi, Gregorio; Madanchi, Mehdi; Bloch, Andreas; Kobza, Richard; Cuculi, Florim (Frontiers in Cardiovascular Medicine, 2022)
Cardiogenic shock (CS) remains a leading cause of hospital death. However, the use of mechanical circulatory support has fundamentally changed CS management over the last decade and is rapidly increasing in Western countries. In contrast to extracorporeal membrane oxygenation as well as counterpulsation with an intraaortic balloon pump, ventricular unloading by the Impella device actively reduces left ventricular volume as well as pressure and augments systemic blood flow at the same time. By improving myocardial oxygen supply and enhancing systemic circulation, the Impella device protects myocardial cells, facilitates ventricular recovery and may interrupt the shock spiral. However, there is only limited and conflicting evidence available regarding the use of the Impella device in CS and further randomized trials are needed. Profound understanding of the device, physiologic impact of device usage and clinical application are all important when considering a patient for percutaneous circulatory support. This review provides a comprehensive overview of the percutaneous assist device, highlights the rationale for ventricular unloading in CS and describes practical aspects to optimize care for patients supported.